A rational system of the own resources for the European Community - Cieślukowski, Maciej (Economics and Business Review, 2005)
A system of EC own resources needs a comprehensive reform because it does not correspond with the new reality of enlarged European Union (EU). The system analysis according to the own resources criteria in federal country proves that the present system of EC resources neither guarantees EC financial autonomy nor equity in taxation between Member States in aid of the general budget. Two main directions of reform are presently considered. First one concerns an extention of EC tax base by creation one or more new EC taxes while second one - a simplification of the system by replacing traditional and VAT resources with so called the fourth resource. The author tries to assess presented lines of reform according to postulated criteria. (original abstract)